Integration of IoT Technology for Assessing the Quality of 3D Printed Parts - TEO, WEI HAO; Marwah, Omar Mohd Faizan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
IR 4.0 is getting more and more popular since it changes the manufacturing process especially with 3d printing and IoT. In order to achieve good quality in 3D printed part IoT which is a new technology that can be used to monitor the parameter and control the printing process. PLA filament is used in this study since it is the most common material used in 3D printed but due to its poor quality, it hasn’t been widely used in industries. Therefore, a IoT monitoring system is used to ensure the parameter fulfill the setting and the quality and properties (surface roughness, dimension deviation, tensile stress) has been studies. The main factor that affects these responses is layer height. The optimum parameter for surface roughness is 0.1 in layer height, 220 printing temperature and 40 printing speed, for dimension deviation is 0.2 in layer height, 220 printing temperature and 40 printing speed while tensile stress is 0.3 in layer height, 200 printing temperature and 60 printing speed. Then an optimization and verification process has been done. The difference between prediction and experiment is below 10% Overall, IoT is a good tool that help to monitor and improve the quality of the 3D printed part.